Oxygen-enriched coal-based porous carbon under plasma-assisted MgCO3 activation as supercapacitor electrodes. (1st February 2022) - Dong, Duo; Zhang, Yongsheng; Xiao, Yi; Wang, Tao; Wang, Jiawei; Gao, Wei
Graphical abstract: Highlights: An eco-efficient plasma-assisted strategy is proposed to manufacture PPC. O functional groups improve the wettability and induce pseudocapacitance of SCs. PPC-5 exhibits ultra-high specific capacitance and remarkable rate performance. The assembled symmetric SCs manifests a prominent energy density. Abstract: Functional carbon materials are used for supercapacitor (SCs) energy storage. Here, an eco-efficient water vapor plasma-assisted MgCO3 activation technology is developed to transform low-grade coal into high-value added porous carbon materials with coordinated regulation of pore structure, specific surface area (SSSA ) and surface characteristics. The surface of coal-based porous carbon modified by water vapor plasma is rough and porous. The pores are interconnected with a three dimensional distribution and conducive for the rapid transport of electrolytes. Moreover, the doping of oxygen atoms improves the wettability of the porous carbon electrode and provides pseudo-capacitance. The obtained modified coal-based porous carbon has a large SSSA, abundant mesopore volume, reasonable pore size distribution and high O/C ratio, resulting in superior performance of SCs. Consequently, the assembled symmetric SCs manifests a superior energy density (10.35 Wh kg −1 ) under power density at 125 W kg −1 and 7.64 Wh kg −1 at 5 kW kg −1 . This work can broaden the application of low-grade coal.